Characteristics of corrosion product films of copper alloy in South China Seawater - Mohammed Misbahul, Amin; Kamaruzzaman, Yunus; Ku Halim, Ku Bulat (Universiti Sains Malaysia & Institution of Chemical Engineers Malaysia, 2009)
Organized by School of Chemical Engineering (USM) & Institution of Chemical Engineers Malaysia, 29th-30th December 2003 at Copthorne Orchid Hotel, Tanjung Bungah, Penang, Malaysia.